Ethnobotany of medicinal plants among the communities of Alpine and Sub-alpine regions of Pakistan. (22nd April 2015) - Kayani, Sadaf; Ahmad, Mushtaq; Sultana, Shazia; Khan Shinwari, Zabta; Zafar, Muhammed; Yaseen, Ghulam; Hussain, Manzoor; Bibi, Tahira
Abstract: Ethno-pharmacological relevance: To best of our knowledge it is first quantitative ethno-botanical study from Alpine and Sub-alpine, Western Himalaya of Pakistan. The study aims to report, compare the uses and highlight the ethno-botanical significance of medicinal plants for treatment of various diseases. Methods: A total of 290 (278 males and 12 females) informants including 14 Local Traditional Healers (LTHs) were interviewed. Information was collected using semi-structured interviews, analyzed and compared by quantitative ethno-botanical indices such as Informant Consensus Factor (ICF), Relative frequency of citation (RFC), use value (UV), Fidelity Level (FL) and Jaccard index (JI). Results: A total of 125 plant species (Gymnosperms 7 species, Monocotyledons 2 and 116 Di-cotyledons) belonging to 41 families are collected, identified and ethno-botanically assessed. The most dominant family is Ranunculaceae (20 species) followed by Rosaceae (14 species). In diseases treated, gastrointestinal tract (GIT) diseases have highest proportion (27.5%) followed by respiratory diseases (20%) in the mountain communities. The most dominant life form of plants used is herbs (78%) followed by shrubs (19%) while the most commonly used plant parts are leaves (44 reports) followed by underground part, the roots (37 reports). The highest ICF (0.68) is found for ear, nose and eye disease category followed by respiratory disorders (0.46). There are 15 medicinal plants having 100% FL. Use value (UV) and Relative frequency of citation (RFC) range from 0.03 to 0.53 and 0.04 to 0.23 respectively. In comparison, maximum similarity index is found in the studies with JI 19.52 followed by 17.39. Similarity percentage of plant uses range from 1.69% to 19.52% while dissimilarity percentage varies from 0% to 20%. Conclusions: The Alpine and Sub-alpine regions of Pakistan are rich in medicinal plants and still need more research exploration. On the other hand, ethno-botanical knowledge in study areas is decreasing day by day due to high emigration rates resulting from after effects of wars during the last few decades. Historically developed ethno-botanical heritage should be preserved and promoted on global level for analyzing phytochemical, pharmaceutical and other biological activities for future drug discovery. Graphical abstract: